Update on syphilis and pregnancy - Tsimis, Michael E.; Sheffield, Jeanne S. (Birth defects research, 2017)
While the origins of syphilis remain unknown, it has long been recognized as an infectious entity with complex pathophysiology. In this review, we highlighted the epidemiology and risk factors associated with syphilis. The incidence of syphilis in most populations showed a consistent upward trend until the 1940s with the introduction of penicillin as the preferred treatment. The emergence of congenital syphilis and vertical transmission has been a direct result of heterosexual syphilis transmission. We also explore the microbiology and pathogenesis of Treponema pallidum as it directly correlates with its route of transmission and infectivity. The clinical features are best categorized into stages (primary, secondary, early, and late latent and tertiary). The primary stage presents as a characteristic chancre and inguinal adenopathy, while the secondary “bacteremia” stage has a predilection to dermatologic manifestations and constitutional symptoms. The latent phase of syphilis witnesses a quiescent period with variable relapse of symptoms and finally, one‐third of untreated patients undergo tertiary syphilis years after the initial infection characterized by severe neurologic or cardiovascular symptomatology. We will also review the data collected for congenital syphilis from the CDC as this can manifest with stillbirth, neonatal death, and nonimmune hydrops. The diagnosis of syphilis focuses on a combination of nontreponemal and treponemal antibody tests with the CDC recommending a traditional algorithm from screening to confirmation. However, other agencies have recently adopted the reverse testing algorithm which has outperformed the traditional algorithm in certain populations. We finally focus on syphilotherapy and monitoring response to treatment with a specific emphasis on pregnancy. Birth Defects Research 109:347–352, 2017. © 2017 Wiley Periodicals, Inc.